Computational investigation of the ligand field effect to improve the photoacoustic properties of organometallic carbonyl clusters. Issue 40 (7th May 2015) - Bag, Arijit; Ghorai, Pradip Kr.
<x xml:space="preserve">Abstract</x> Organometallic nitrosyl carbonyl clusters are stable and better high-contrast photoacoustic contrast agents (PACAs) than organometallic carbonyl clusters.